Effects of soybean cultivar and starter strain on biogenic amines formation during Cheonggukjang fermentation - BaoZhu Shi; BoKyung Moon (Food Chemistry: X, 2024)
Cheonggukjang, a traditional Korean fermented seasoning, contains biogenic amines (BAs). This research aimed to explore the effects of soybean cultivar, strain, and temperature on BAs formation during Cheonggukjang fermentation. Moisture, pH, total aerobic plate count, and protease activity were measured. Free amino acids (FAAs) and BAs were determined by high-performance liquid chromatography. Total FAA and BA contents tended to increase with fermentation time. Total BAs in the samples initially ranged from 112.65 to 153.05 mg/kg and ultimately increased to 155.72–614.28 mg/kg at 25 °C and 201.95–738.39 mg/kg at 37 °C, respectively. Bacillus licheniformis-inoculated samples had the highest total BA content (over 400 mg/kg) after 96 h of fermentation. Final histamine content in cv. ‘Somoktae’-made samples generally exceeded that in samples produced by the other two cultivars. These findings indicate that soybean cultivar, strain, and fermentation temperature all play pivotal roles in controlling the contents of BAs in Cheonggukjang.